Development of Sustainable Timber Construction in Ibero-America: State of the Art in the Region and Identification of Current International Gaps in the Construction Industry - Araya, Raúl (2022)
This article presents the latest developments of the Spanish- and Portuguese-speaking countries of Europe and Latin America towards the development of sustainable timber construction. As most regions related to these countries have not traditionally employed timber as primary construction material, bringing the development of sustainable timber construction into fruition requires a wide range of actions, such as the elaboration of new educational programs, construction of demonstrative buildings, dissemination activities, settlement of public policies, elaboration of new construction codes, and the creation of new certification bodies. This article presents an overview of the state of the development of the different countries of Ibero-America, showing a very uneven development in the region. In addition to national analyses, a perception survey of 233 professionals from different countries was conducted, allowing for the identification of good practices, present gaps, and opportunities, as well as barriers for developing sustainable timber construction. It is concluded that in order to promote the development of the timber construction industry in the region, it is necessary to progress on regulatory, cultural, and material availability issues, where international experience, demonstrative buildings, and the implementation of public policies are crucial.